Feasibility Of Bitter Melon Masks For Anti-Aging Facial Skin Care - Azhari, Nadya; Rosalina, Linda (PT. Hafasy Dwi Nawasena, 2024)
This study aims to evaluate the feasibility of using bitter melon (Momordica charantia) mask as an anti-aging facial skin treatment through a quantitative research method with an experimental approach. This research is important because anti-aging skincare aims to prevent premature ageing, which is often caused by factors such as exposure to free radicals and oxidative stress. The feasibility of bitter melon masks was evaluated through a series of tests, including laboratory tests to measure flavonoid, phenolic, and collagen content, as well as organoleptic and hedonic tests to assess physical characteristics and user preferences. Data collection techniques involved observation, documentation, and the use of observation sheets. Laboratory test results showed that the bitter melon mask contained positive flavonoids, phenolic compounds, and collagen, which are known to be beneficial for skin health and ageing prevention. Meanwhile, the organoleptic and hedonic test results showed that the bitter melon mask had a smooth texture, distinctive bitter melon aroma, strong adhesion, and was quite liked by the panellists. Based on these findings, the bitter melon mask is considered suitable for use as an anti-aging facial skincare product.